Gathering Pandanus Leaves: Colonization, Internationalization and the Pacific - Naepi, Sereana; Leenen-Young, Marcia (Journal of International Students, 2021)
It has long been established that education is both a colonial and imperial tool that enables colonizing nations to establish themselves in foreign territories. This paper explores New Zealand’s historical and contemporary role in the Pacific and how the country has leveraged higher education to both strengthen and continue its ongoing colonial and imperial projects. Utilizing current understandings of critical internationalization this paper will examine the lengths that New Zealand has gone to in order to protect its international standing as a gateway to the Pacific.